2005
DOI: 10.1002/qsar.200420065
|View full text |Cite
|
Sign up to set email alerts
|

Split‐Plot Experimental Designs for Combinatorial and High‐Throughput Experimentation

Abstract: In the last few years, high-throughput reactors have small received significant attention due to the potential they offer for fast material development. While many experimental design techniques are proposed, statistical issues related to experimentation in this type of equipment are emerging. One of the experimental design techniques needed is the split-plot approach, given the randomization restrictions imposed by the equipment. This paper presents the use of split-plot experimental designs in a high-through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…A clear drawback is the large number of experiments to be carried out, which rapidly increases with the number of selected factors. Castillo et al [14] presented the use of a splitplot experimental design, developed for high-throughput studies of catalysts (see Figure 2 in Ref. [14]), but demonstrated this with only two catalysts.…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
See 1 more Smart Citation
“…A clear drawback is the large number of experiments to be carried out, which rapidly increases with the number of selected factors. Castillo et al [14] presented the use of a splitplot experimental design, developed for high-throughput studies of catalysts (see Figure 2 in Ref. [14]), but demonstrated this with only two catalysts.…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
“…Castillo et al [14] presented the use of a splitplot experimental design, developed for high-throughput studies of catalysts (see Figure 2 in Ref. [14]), but demonstrated this with only two catalysts. Here two levels of the parameters temperature (T) and pressure (p) were combined with the variation of two catalysts at two concentrations.…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
“…Several studies have been reported on the generation of catalyst libraries of multi-component catalysts for catalytic reaction explorations. [129][130][131][132] Among various techniques, inkjet printing has been reported to be a powerful tool for the rapid synthesis of catalyst nanomaterials. 94,133,134 Normally the catalyst species precursors are prepared in the form of inks and a variety of composition ratios can be produced by changing the gradient of designed patterns.…”
Section: Fast Catalytic Probementioning
confidence: 99%
“…Ein offenkundiger Nachteil ist die große Zahl der auszuführenden Experimente, die mit der Anzahl der ausgewählten Parameter schnell ansteigt. Castillo et al [14] beschrieben die Verwendung eines experimentellen Split-Plot-Designs, das für HT-Studien an Katalysatoren (siehe Abbildung 2 in Lit. [14]) entwickelt wurde, demonstrierten dies jedoch anhand von nur zwei Katalysatoren.…”
Section: Experimentelles Design (Doe Design Of Experiments)unclassified
“…Castillo et al [14] beschrieben die Verwendung eines experimentellen Split-Plot-Designs, das für HT-Studien an Katalysatoren (siehe Abbildung 2 in Lit. [14]) entwickelt wurde, demonstrierten dies jedoch anhand von nur zwei Katalysatoren. Hier werden zwei Werte der Parameter Temperatur (T) und Druck (p) mit der ¾nderung von zwei Katalysatoren in zwei Konzentrationen kombiniert.…”
Section: Experimentelles Design (Doe Design Of Experiments)unclassified